Seder Tefilot mi-kol ha-shanah: ʿim lashon Ashkenaz : ke-minhag Ashkenazim - Lamsvelt, Jan; Proops, Solomon ben Joseph - (bi-defus ... Shelomoh ben ... Yosef Kats .... Props ... mokher sefarim, 1714)
Gebetbuch für das ganze Jahr nach deutschem Ritus